Сутність професійної підготовки майбутніх магістрів фізичної культури та спорту до організації оздоровчих і спортивних заходів - Резнік, Світлана Миколаївна; Євтифієв, Андрій Сергійович (Полтавська академія неперервної освіти імені М. В.Остроградського, 2025)
На основі теоретичного аналізу визначено поняття організації, організатора, а також спільні та відмінні особливості проведення заходів для професійних спортсменів і широких верств населення. Майбутнього магістра фізичної культури та спорту як організатора визначено як особистість, що у складі організаційного комітету (команди), зокрема як ініціатор, здатна до впорядкування всіх необхідних дій та елементів, що забезпечують підготовку і проведення оздоровчих і спортивних заходів. Визначено, що професійна підготовка майбутнього магістра фізичної культури та спорту до організації оздоровчих і спортивних заходів – це складний, системний процес формування професійно-важливих знань, умінь, навичок, особистісних якостей, які забезпечують готовність майбутнього фахівця успішно впорядковувати дії, необхідні для ефективного проведення відповідних заходів. Based on the theoretical analysis, the article defies the concepts of "organization" and "organizer", and the common and distinctive features of holding events for professional athletes and the general population. The future Master of Physical Culture and Sports, as an organizer, is defied as a person who, as part of the organizing committee (team), including as an initiator, can streamline all the necessary actions and elements, ensuring the preparation and conduct of health and sports events. Common features of the organization of such events are the promotion of physical culture and sports; ensuring interest in increasing physical activity and a healthy lifestyle among the population; considering the tasks and purpose of the event, the age and capabilities of the participants, the scale of the event, the sport(s) involved, etc.; fostering certain character traits (resilience, endurance, balance, courage, willpower, perseverance, determination, etc.); personal development; ensuring entertainment and aesthetics appeal; and planning and implementation of all stages and components of the event (informational, fiancial, logistical, medical support, etc.). Distinctive features of events for professional athletes include stricter, regulated rules and norms; and the selection of stronger athletes for further participation in competitions, etc. Distinctive features of events for the general population include simplifid rules of conduct; assistance in improving participants' physical and mental state; a greater variety of forms and types of activities, etc. It is determined that the professional training of the future Master of Physical Culture and Sports for the organization of health and sports events is a complex, systematic process that involves the formation of professionally important knowledge, skills, and personal qualities necessary for ensuring the readiness of the future specialist to successfully organize the actions required for the effctive implementation of relevant events.
The essence of professional training of future masters in physical education and sports for organizing health and sports events
Keywords: професійна підготовка; майбутні магістри; майбутні фахівці фізичної культури та спорту; організація оздоровчих і спортивних заходів; організатор; professional training; future masters; future specialists in physical culture and sports; organization of health and sports events; organizer